Children's perception of breathlessness in acute asthma. Issue 4 (1st October 2000) - Male, I; Richter, H; Seddon, P
Abstract : AIM: To determine whether asthmatic children who present to hospital with hypoxia perceive breathlessness less well than non-hypoxic presenters. METHODS: A total of 27 children aged 5–16 years (mean age 10) admitted with acute asthma had recordings of oxygen saturation (Sao 2 ), clinical score, forced expiratory volume in one second (FEV1 ), and breathlessness score (HMP) at admission and at 5, 10, 24, 48, and 72 hours after admission. Those defined as hypoxic (Sao 2 <92%) at admission were compared with a non-hypoxic group. RESULTS: Twelve children were hypoxic at admission. Compared with the non-hypoxic group they were younger (8.6 (SD 2.8) v 11.2 (2.8) y, p = 0.02), and had greater airway obstruction (FEV1 32.5 (10)% v 54.3 (26)%, p = 0.0073, 95% confidence interval (CI) −36.9 to −6.6) yet had a trend towards less breathlessness (median HMP 4 v 3, p = 0.062, CI −0.001 to 2.00) at admission. The hypoxic group had a smaller change in breathlessness from admission to discharge, despite a similar improvement in FEV1, reflected in a lower ratio of change in HMP to change in FEV1 (ΔHMP/ΔFEV1 ) (median ΔHMP/ΔFEV1 0.021% −1 v 0.073% −1, p = 0.0081, CI −0.075 to −0.016). Linear regression analysis showed a strong relation between ΔHMP/ΔFEV1 and initial Sao 2 (p = 0.004, r = 0.54). CONCLUSIONS: Asthmatic children who present to hospital hypoxic tend to perceive themselves as less breathless than non-hypoxic children. This may predispose to a future life threatening attack.